2010
DOI: 10.1007/s12550-010-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various surfactants (cationic, anionic and non-ionic) on the growth of Aspergillus parasiticus (NRRL 2999) in relation to aflatoxin production

Abstract: The effect of surfactants (two cationic, one anionic and three non-ionic) at 0.001, 0.01, 0.1 and 1.0 % concentrations on aflatoxin production, ergosterol content and sugar consumption by Aspergillus parasiticus (NRRL 2999) in YES liquid culture medium is reported. At 0.01% concentration, the cationic surfactants, cetyl dimethyl ammonium bromide (CDAB) and dodecyl trimethyl ammonium bromide (DTAB), and the anionic surfactant, sodium dodecyl sulfate (SDS), completely inhibited spore germination, while DTAB also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…bassiana. Results of the growth inhibition of B. bassiana in the additives were in accordance with those of Tanuja et al (2010) who stated that the negative impact of surfactants to microorganism was probably due to increased cell permeability and amino acid leakage through inner membrane. Formulation of myco-insecticide must be compatible with the agent and must enhance its performance and, ideally, must maintain an adequate shelf-life of the agent in order to be successful (Derakhshan et al 2008).…”
Section: B) Spore Loadsupporting
confidence: 87%
“…bassiana. Results of the growth inhibition of B. bassiana in the additives were in accordance with those of Tanuja et al (2010) who stated that the negative impact of surfactants to microorganism was probably due to increased cell permeability and amino acid leakage through inner membrane. Formulation of myco-insecticide must be compatible with the agent and must enhance its performance and, ideally, must maintain an adequate shelf-life of the agent in order to be successful (Derakhshan et al 2008).…”
Section: B) Spore Loadsupporting
confidence: 87%
“…Selected surfactants have been shown by Chen et al, (2006) to restrain the degradation of polycyclic aromatic hydrocarbons by white-rot fungi. In other related studies, surfactants have been shown to inhibit spore germination and ergosterol production by fungi (Kozirog et al, 2018;Mwamburi et al, 2015;Tanuja et al, 2010). It can thus be generalized that surfactants puts a pressure on the hydrocarbon degrading ability of fungi, and this pressure can be relaxed in the presence of nutrients as observed in this study.…”
Section: Peekate Pl; Konne Jl; Abam Tkssupporting
confidence: 69%
“…However, the biomass decreased rapidly after day 8 due to the negative effect, i.e. damaging the cell membrane, on the cell growth after long‐time reaction or long‐time harmful interaction with other bio‐components in cells 22 …”
Section: Resultsmentioning
confidence: 99%